REPRESENTASI PEREMPUAN DALAM IKLAN SUSU JAHE SIDO MUNCUL VERSI SIDO SUSU - Dyah Ratmasanti, Ni Nyoman Irafani; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2020)
ABSTRACT Susu Jahe Sido Muncul Sido Susu version is an advertisement that illustrates how the mass media still uses sensuality and exploitation of women as a means to attract the attention of the audience. This ad contains information about the